IS ECONOMICS A HOUSE DIVIDED? ANALYSIS OF CITATION NETWORKS. - Önder, Ali Sina; Terviö, Marko (Economic Inquiry, 2015)
We investigate divisions within the citation network in economics using citation data between 1990 and 2010. We consider all partitions of top institutions into two equal-sized clusters and pick the one that minimizes cross-cluster citations. The strongest division is much stronger than could be expected to be found under idiosyncratic citation patterns and is consistent with the reputed freshwater/saltwater division in macroeconomics. The division is stable over time but varies across the fields of economics. ( JEL A11, D85, I23)